Histamine receptors influence blood-spinal cord barrier permeability, edema formation, and spinal cord blood flow following trauma to the rat spinal cord - Sharma H.S.; Vannemreddy P.; Patnaik R.; Patnaik S.; Mohanty S. (My University, 2025)
The role of histamine in edema formation, blood-spinal cord barrier (BSCB) permeability, and spinal cord blood flow (SCBF) following spinal cord injury (SCI) was examined using modulation of histamine H1, H2, and H3 receptors in the rat. Focal trauma to the spinal cord at the T10-11 level significantly increased spinal cord edema formation, BSCB permeability to protein tracers and SCBF reduction in the T9 and T12 segments. Pretreatment with histamine H1 receptor antagonist mepyramine (1 mg, 5 mg, and 10 mg/kg, i.p.) did not attenuate spinal pathophysiology following SCI. Blockade of histamine H2 receptors with cimetidine or ranitidine (1 mg, 5 mg, or 10 mg/kg 30 minutes before injury) significantly reduced early pathophysiological events in a dose dependent manner. The effects of ranitidine were far superior to cimetidine in identical doses. Pretreatment with a histamine H3 receptor agonist α-methylhistamine (1 mg and 2 mg/kg/i.p.), that inhibits histamine synthesis and release in the CNS, thwarted edema formation, BSCB breakdown, and SCBF disturbances after SCI. The lowest dose of histamine H3 agonist was most effective. Blockade of histamine H3 receptors with thioperamide (1 mg, 5 mg/kg, i.p.) exacerbated spinal cord pathology. These observations suggest that stimulation of histamine H3 receptors and blockade of histamine H2 receptors is neuroprotective in SCI. © 2006 Springer-Verlag.